مساهمة الاتصال الاداري في تفعیل الاداء الوظیفي دراسة ميدانية بمطاحن بلغيث الكبرى بمداوروش - رجم هاجر (My University, 2019)
Study Summary: This study falls within the descriptive category, examining "the contribution of administrative communication to enhancing job performance." In this study, we relied on a sample survey approach, employing a purposive stratified sample. The sample size was 20 workers from the Belghith Mills Company in Madaoua. We used a questionnaire as the primary tool, supplemented by observation to verify the accuracy of the information. The study reached a set of important results, which can be summarized as follows: Good administrative communication among employees in the company contributes to enhancing job performance. Administrative communication barriers lead to poor employee performance. Failure to consider individual psychological well-being, the lack of modern technologies within the organization, and the lack of a suitable work environment all contribute to the failure of communication, which in turn leads to poor employee performance. Employee participation in decision-making and activities necessarily leads to a commitment to optimal implementation, thus ensuring effective job performance. ------------------------ ملخص الدراسة: تندرج هذه الدراسة ضمن إطار البحث الوصفي، حيث تتناول "مساهمة التواصل الإداري في تحسين الأداء الوظيفي". اعتمدت الدراسة على منهج المسح بالعينة، مستخدمةً عينة طبقية قصدية. بلغ حجم العينة 20 عاملاً من شركة مطاحن بلغيث في ماداوا. استخدمنا استبياناً كأداة رئيسية، وأُضيفت إليه الملاحظة للتحقق من دقة المعلومات. توصلت الدراسة إلى مجموعة من النتائج المهمة، يمكن تلخيصها فيما يلي: يساهم التواصل الإداري الجيد بين موظفي الشركة في تحسين الأداء الوظيفي. تؤدي عوائق التواصل الإداري إلى ضعف أداء الموظفين. إن عدم مراعاة الصحة النفسية للأفراد، ونقص التقنيات الحديثة داخل المؤسسة، وعدم توفر بيئة عمل مناسبة، كلها عوامل تُسهم في فشل التواصل، مما يؤدي بدوره إلى ضعف أداء الموظفين. إن مشاركة الموظفين في صنع القرارات والأنشطة تؤدي بالضرورة إلى الالتزام بالتنفيذ الأمثل، مما يضمن أداءً وظيفياً فعالاً.
Keywords: الاتصال الاداري، الاداء الوظیفي